Effects of different detergent-containing children's toothpastes on the viability, osteogenic and chondrogenic differentiation of human dental periodontal ligament stem cells and gingival stem cells in vitro - AKKOÇ, TUNÇ (CHURCHILL LIVINGSTONE, 2021)
Background: Detergents are the most commonly used compounds in toothpastes due to their foaming and cleaning peoperties. This study aimed to investigate the effects of children's toothpastes with different detergent content on the viability, the osteogenic and chondrogenic differentiation potentials of human mesenchymal stem cells. Methods: The necessary tissues for human periodontal ligament mesenchymal stem cells (hPDLMSCs) and human gingival mesenchymal stem cells (hGMSCs) isolation were obtained during extraction of 10 impacted third molar teeth. The viability of the cells stimulated with different concentratiaons of Colgate, Sensodyne, Splat, Nenedent, Perlodent toothpaste solutions and complete Dulbocco's modified eagle medium (control group) were evaluated by using the flow cytometer. In addition, the osteogenic and chondrogenic differentiation potential of human gingival and periodontal ligament mesenchymal stem cells exposed to toothpaste solutions were examined morphologically. Datas were analyzed with IBM SPSS V23. One way ANOVA test was used to determine the differences between the groups for multiple comparisons, while the Tukey post-hoc test was used for pair wise comparisons in determining which groups differed. Results: A higher percentage of cell viability was detected in Control group at 20 %, 50 % and 80 % (p= 0.000) on hGMSCs. After the Control group, the highest cell viability ratios were observed in the detergent-free Splat group (p = 0.000) followed by the Sensodyne experimental group containing CABP (p= 0.000). While the cell viability rates in Nenedent group was found significantly higher than the Perlodent group at other concentrations except for 20 % concentration (p = 0.000). Colgate group had the lowest percentage of cell viability among the experimental groups at all concentrations on hPDMSCs (p = 0.000). The highest live cell ratios was detected in Control group (p = 0.000), followed by Splat and Sensodyne groups (p = 0.000). The cell viability ratios at 50 % concentration were higher in Perlodent group than Nenedent group (p = 0.000). The highest osteogenic and chondrogenic differentiation potential of mesenchymal stem cells stimulated with different toothpaste was determined in Control and Splat group. Conclusions: As a result of the findings, it was observed that toothpaste containing SLS had a more negative effect on the viability of the cells and the differentiation potentials than the other groups.
Keywords: Toothpaste; Stem cell; Anneksin V; Detergent; SLS; SODIUM LAURYL SULFATE; HUMAN ORAL-MUCOSA; DENTIFRICES; BETAINE; PERMEABILITY; APOPTOSIS; REPAIR; PLAQUE